PELATIHAN CORE STABILITY DAN BALANCE BOARD EXERCISE LEBIH BAIK DALAM MENINGKATKAN KESEIMBANGAN DIBANDINGKAN DENGAN BALANCE BOARD EXERCISE PADA MAHASISWA USIA 18 – 24 TAHUN DENGAN KURANG AKTIVITAS FISIK - Berbudi BL, Abdurahman; Adiputra, N.; -, Sugijanto (Sport and Fitness Journal, 2014)
Sedentary Lifestyle has negative impact on health that would lead to overweight or obesity, where it will also lead to impaired balance and risk of falling even cause bodily injury, to improve the physical activity it should be improved, and also to improve the balance there are some exercises such as core stability and balance board. The purpose of this study was to analyze whether core stability exercises and balance board exercise in improving balance better than the balance board exercise on students aged 18-24 years with less physical activity. This research design using experimental research methods pre and post study design. Where the samples were obtained 28 in total obtained from the results of systematic random sampling. In the first group conducted joint exercises core stability and balance board (n = 14). The second group was only exercise balance board. Characteristics of the study subjects obtained a mean value of physical activity in the group of core stability exercises and balance board (314.68) Mets-minute/week, and the mean value of the balance before in group 1 (14.00 s) in the group balance board (286.4) Mets-minute/week. and the mean value of the balance before (11.56 s). data obtained from the above then tested using the Shapiro Wilk normality is found that the core stability and balance board p <0.05, the data are not normally distributed, the balance board group obtained a p value> 0.05 then the data were normally distributed. Different test groups before and after the core stability and balance board using the Wilcoxon signed rank test p value = 0.001 is obtained. p<0.05. Different test groups before and after the balance board by using paired sample test found p value = 0.0002 p<0.05 then get a meaningful result there are significant differences. Conclusions in this study showed that the treatment group core stability and balance board compared with the only balance board can increase the value of the balance standing stork test students with less physical activity.
Keywords: Balance, Physical Activity, Core Stability, Balance Board.